Factors Predicting Testicular Atrophy after Testicular Salvage following Torsion - Lian, Bertrand S. Y.; Ong, Caroline C. P.; Chiang, Li Wei; Rai, Rambha; Nah, Shireen Anne (European Journal of Pediatric Surgery, 2016)
Introduction Testicular atrophy (TA) is a significant complication in patients who undergo salvage procedures for testicular torsion. Studies on outcome focus on factors predicting testicular viability during scrotal exploration but few assess factors predicting TA in patients who undergo salvage procedures. We assess the incidence of TA after salvage and identify associated factors.Materials and Methods With ethical approval, we reviewed patients who underwent salvage for testicular torsion in our institution from 2001 to 2013. Data was collected on patient demographics, duration of pain, sonographic findings, postoperative complications, and follow-up assessment of TA (defined as difference in testicular volume > 50% compared with the contralateral testis, based on measurement by Prader orchidometer or by ultrasound). We excluded patients with torted undescended testis, those under 1 month, and those with follow-up < 6 months. Chi-square or Mann–Whitney U tests were used as appropriate with significance level < 0.05.Results Of 85 patients who had scrotal exploration for testicular torsion, 53 had testicular salvage. Overall, 16 patients defaulted or had < 6 months follow-up, leaving 37 patients who were studied, median age 12 years (range, 0.5–16.0 years) at presentation. Median follow-up was 12.5 months (range, 6–88 months). A total of 20 patients (54%) developed TA. Median duration to TA was 12.5 months (range, 2–88 months). All had clinical evidence of atrophy by 14 months, except two who initially defaulted follow-up, but were diagnosed with TA at 35 and 88 months postoperatively when presenting with unrelated complaints. Factors associated with TA were duration of pain > 1 day (p = 0.004) and heterogeneous echogenicity on ultrasound (p = 0.001). Sonographic evidence of reduced vascularity was not predictive. Of 11 that had pain > 1 day, 10 (91%) had TA. No testes survived when pain ≥ 3 days.Conclusion Half of patients with testicular torsion undergoing salvage surgery will develop testicular atrophy, even when intraoperatively assessed as viable, and should be counseled accordingly. Duration of pain > 1 day and sonographic heterogeneous echogenicity are predictive. Salvage rates are dismal when duration of symptoms exceeds 1 day.
Keywords: testicular preservation; orchidectomy; testicular hypotrophy